Book Review: Byzantine Military Rhetoric in the Ninth Century. A Translation of the Anonymi Byzantini Rhetorica Militaris, London -New York 2021 - RóżYCKI, Łukasz (Byzantina Symmeikta, 2021)
Byzantine Military Rhetoric in the Ninth Century. A Translation of the Anonymi Byzantini Rhetorica Militaris, trans. Georgios Theotokis, Dimitrios Sidiropoulos, London – New York 2021.